Small Christian communities in Eastern Africa: with particular reference to Tanzania; canonical implications - Mringi, Augustine (1984)
Im Mittelpunkt stehen kleine, christliche Vereinigungen in Ostafrika, die im kanonischen Kontext betrachtet werden